Combined Treatment of Tanshinone I and Epirubicin Revealed Enhanced Inhibition of Hepatocellular Carcinoma by Targeting PI3K/AKT/HIF-1α - Zhao J; Lin E; Cai C; Zhang M; Li D; Cai S; Zeng G; Yin Z; Wang B; Li P; Hong X; Chen J; et al. (Dove Medical Press, 2022)
Jiali Zhao,1 En Lin,1 Chaonong Cai,1 Manyao Zhang,2 Decheng Li,1 Shanglin Cai,1 Guifang Zeng,1 Zeren Yin,1 Bo Wang,1 Peiping Li,1 Xiaopeng Hong,1 Jiafan Chen,1 Baojia Zou,1 Jian Li1 1Department of Hepatobiliary Surgery, Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, People's Republic of China; 2Department of Anesthesiology, Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, People's Republic of ChinaCorrespondence: Jian Li; Baojia Zou, Department of Hepatobiliary Surgery, Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, People's Republic of China, Tel +86-756-252-8781, Fax +86-756-252-8166, Email lijian5@mail.sysu.edu.cn; zoubj6@mail.sysu.edu.cnBackground: Epirubicin (EADM) is a common chemotherapeutic agent in hepatocellular carcinoma (HCC). The accumulation of hypoxia-inducible factor-1α (HIF-1α) is an important cause of drug resistance to EADM in HCC. Tanshinone I (Tan I) is an agent with promising anti-cancer effects alone or with other drugs. Some tanshinones mediate HIF-1α regulation via PI3K/AKT. However, the role of Tan I combined with EADM to reduce the resistance of HCC to EADM has not been investigated. Therefore, this study aimed to investigate the combined use of Tan I and EADM in HCC and the underlying mechanism of PI3K/AKT/HIF-1α.Methods: HCC cells were treated with Tan I, EADM, or the combined treatment for 48 hrs. Cell transfection was used to construct HIF-1α overexpression HCC stable cells. Cell viability, colony formation, and flow cytometric assays were used to detect the viability, proliferation, and apoptosis in HCC cells. Synergism between Tan I and EADM were tested by calculating the Bliss synergy score, positive excess over bliss additivism (EOBA), and the combination index (CI). Western blotting analyses were used to detect the levels of β-actin, HIF-1α, PI3K p110α, p-Akt Thr308, Cleaved Caspase-3, and Cleaved Caspase-9. Toxicity parameters were used to evaluate the safety of the combination in mice. The xenograft model of mice was built by HCC stable cell lines, which was administrated with Tan I, EADM, or a combination of them for 8 weeks. Immunohistochemistry staining (IHC) was used to assess tumor apoptosis in mouse models.Results: Hypoxia could upregulate HIF-1α to induce drug resistance in HCC cancer cells. The combination of Tan I and EADM was synergistic. Although Tan I or EADM alone could inhibit HCC cancer cells, the combination of them could further enhance the cytotoxicity and growth inhibition by targeting the PI3K/AKT/HIF-1α signaling pathway. Furthermore, Tan I and EADM synergistically reversed HIF-1α-mediated drug resistance to inhibit HCC. The results of toxicity parameters showed that the combination was safe in mice. Meanwhile, animal models showed that Tan I not only improved the anti-tumor effect of EADM, but also reduced the drug reactions of EADM-induced weight loss.Conclusion: Our results suggested that Tan I could effectively improve the anti-tumor effect of EADM, and synergize EADM to reverse HIF-1α mediated resistance via targeting PI3K/AKT/HIF-1α signaling pathway.Keywords: hepatocellular carcinoma, epirubicin, Tanshinone I, HIF-1α, resistance